Systematic Review of the Pharmacological Evidence for the Selection of Antimicrobials in Bacterial Infections of the Central Nervous System in Dogs and Cats - Hertzsch, Robert; Richter, Angelika (Frontiers in Veterinary Science, 2022)
Bacterial meningitis in dogs and cats is a rare disease associated with a high lethality rate. The spectrum of causative bacteria includes a diverse set of gram positive, gram negative and anaerobic species. Currently, no veterinary medicinal product is approved for this indication in these species in Europe. The objective of this review was to collect the available pharmacokinetic data for antibiotics approved in dogs and cats to enable a preliminary analysis of their potential effectiveness for the treatment of bacterial meningitis. This analysis yielded data for 13 different antibiotics in dogs and two in cats. Additionally, data about frequently recommended cephalosporines not approved in dogs and cats were included. The collected data was used to assess the potential of the respective antibiotics to attain certain simple pharmacokinetic-pharmacodynamic (PK-PD) indexes in the cerebrospinal fluid (CSF). A more sophisticated investigation using modern methods was not possible due to the limited data available. For this purpose, data about the sensitivity of four bacterial species commonly associated with meningitis in dogs and cats to these antibiotics were included. The analysis provided evidence for the potential effectiveness of ampicillin, doxycycline, enrofloxacin, ceftriaxone and cefoxitin against bacteria frequently detected in bacterial meningitis in dogs. Data were not available or insufficient for the assessment of several antibiotics, including frequently recommended substances like metronidazole and trimethoprim-sulphonamide. Little evidence is available for the use of antibiotics in cats afflicted with this disease, highlighting the need for further research to obtain data for evidence based therapeutic recommendations.